2019
DOI: 10.1177/1129729819854009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of yield and complications of craniocaudal versus caudocranial needle trajectory for kidney biopsy

Abstract: Background: Percutaneous renal biopsy can result in serious complications. The study is aimed to compare the safety and yield between the two approaches of biopsy techniques: the conventional craniocaudal and the caudocranial trajectory of the biopsy needle under real-time ultrasound guidance. Methods: In this prospective observational study, a total of 80 serial kidney biopsies were performed, 40 with craniocaudal angulation and 40 with caudocranial angulation of the biopsy needle on the random allocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a previous study comparing the craniocaudal approach and the angled tangential approach (i.e., the vertical approach used in this study), the angled tangential approach collected significantly more glomeruli [20]. In several studies comparing the caudocranial and craniocaudal approaches, there was no significant difference in the number of glomeruli collected [16, 26]. Our study differed from previous reports in that all approaches were performed on the same kidney and our results were similar; there was no significant difference between the caudocranial and craniocaudal approaches, and the vertical approach yielded significantly more glomeruli than the other two approaches.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In a previous study comparing the craniocaudal approach and the angled tangential approach (i.e., the vertical approach used in this study), the angled tangential approach collected significantly more glomeruli [20]. In several studies comparing the caudocranial and craniocaudal approaches, there was no significant difference in the number of glomeruli collected [16, 26]. Our study differed from previous reports in that all approaches were performed on the same kidney and our results were similar; there was no significant difference between the caudocranial and craniocaudal approaches, and the vertical approach yielded significantly more glomeruli than the other two approaches.…”
Section: Discussionmentioning
confidence: 72%
“…Three main approaches to kidney biopsy are commonly usednamely, puncturing the lower pole toward the cranial side, puncturing the lower pole toward the caudal side, and puncturing the surface cortex of the lower pole of the kidney. To date, several reports have presented the advantages of each approach [14][15][16][17] and have evaluated their postoperative bleeding risk. However, these studies were not performed on the same kidney; it is not ethical in clinical practice to use different approaches at the same time on a single individual.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Other retrospective and prospective observational studies revealed the caudal angulation needle approach under real-time ultrasonogram guidance in obtaining cortical tissue from the lower pole of the native kidney as an effective technique with very few complications. 6 , 7 Hence, our study is the first human RCT that compared CD to CN in native kidney biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The key exclusion criteria were (1) patients who underwent a kidney transplant, (2) serum creatinine of >3.5 mg/dL for 3 months, (3) small-size kidneys (length of <8 cm, width of <3.5 cm), (4) coagulopathy and/or thrombocytopenia, (5) uncontrolled hypertension (>160/100 mmHg), ( 6) obesity (body mass index [BMI] of >35 kg/m 2 ), (7) single kidney, and (8) refusal to sign the inform consent. The full exclusion list was announced at the Thai Clinical Trial Registry (TCTR20170706001: https://www.thaiclinicaltrials.org/show/TCTR20170706001).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation